Isolation and functional characterisation of the PHT1 gene encoding a high-affinity phosphate transporter in Camellia oleifera. Issue 5 (2nd September 2020) - Zhou, Junqin; Lu, Mengqi; Zhang, Chenhui; Qu, Xinjing; Liu, Yiyao; Yang, Jin; Yuan, Jun
ABSTRACT: Phosphate (Pi) transporters in plants mediate phosphorus (P) acquisition, translocation and recycling. In this study, a putative high-affinity Pi transporter gene ( CoPht1;3, GenBank KF989483.1) was isolated and characterised from oil-tea tree ( Camellia oleifera Abel .). The CoPht1;3 contained a 1575-bp open reading frame encoding 525 amino acid residues. It shared 98.67%, 88.50%, 86.50%, and 85.60% amino acid identities with the Pht1s of Camellia sinensis, Camelina sativa, Arabidopsis thaliana and Hevea brasiliensis, respectively. The CoPht1;3 exhibited all essential motifs and 12 transmembrane helix common to the Pht1 family of Pi transporters, in which α-helical structure accounted for 48.66% in protein. The CoPht1;3 was localised in tonoplast detected by transient expression of CoPht1;3:eGFP in tobacco epidermal cells. Quantitative real-time PCR showed that CoPht1;3 mRNA was detected in root, leaf and stem, but its transcript was most abundant in young leaves under low P supply. The results suggested that CoPht1;3 might be a high P affinity transporter. CoPht1;3 overexpression enhanced absorption of P and increased biomass of the transgenics. CoPht1;3 may play a key role in the transportation process of P in oil-tea tree leaves and could be targeted as a candidate gene to improve oil-tea tree P efficiency.